Role of wind speed and solar irradiation on the cost of medium-sized off-grid hybrid renewable energy systems under challenging weather conditions - MohammadReza Akhtari; Oskar Karlström (Energy Conversion and Management: X, 2025)
The present study investigates the role of wind speed and solar irradiation on the cost of medium-sized energy systems under weather conditions characterised by long winters and summers with extended sunlight hours. The study models and optimises different configurations of off-grid hybrid energy systems for 100 persons for conditions of 20 different cities, using hourly input data of solar irradiation, ambient temperature, and wind speed. In total, more than 500,000 data points are used in the multi-variable optimisation. In these cities, the average (throughout the year) wind speed varies between 2.32 and 7.23 m/s, and the solar irradiation varies from 1.94 to 3.61 kWh/m2/day. The winters for the investigated cities are long (several months), with solar irradiation less than 0.5 kWh/m2/day. The optimised systems consist of small-scale wind energy, solar energy, batteries, and biodiesel generators as backup energy. For the optimised systems with wind energy, the results show that the levelized costs range between 0.16 and 0.48 $/kWh. For the optimised systems without wind energy, the cost ranges from 0.44 to 0.63 $/kWh. These results give new insight into when additional energy sources may be needed in medium-sized energy systems. Finally, a sensitivity analysis shows that even small-scale off-grid systems without wind energy may soon be a viable option for reaching competitive energy prices with existing technologies.